Lithium metal negative electrode and preparation method and application thereof

CN122930840APending Publication Date: 2026-10-16NINGBO RONBAY LITHIUM BATTERY MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610946139.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-26
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

但锂金属负极在实际工况下仍存在界面接触差、界面阻抗偏高,易与固态电解质发生界面副反应,且充放电过程中极易诱发锂枝晶无序生长,进而造成电池倍率性能衰减、循环寿命缩短,严重损害电池的循环使用安全性

Benefits of technology

[0032]本申请实施例提供的锂金属负极,锂金属层的厚度方向上依次层叠设置的锂传输层、钝化层与柔性层构成保护层。其中,锂传输层实现锂离子的快速传导,钝化层为界面提供化学稳定性并起到物理阻隔锂枝晶穿刺作用;柔性层则改善与固态电解质的界面贴合状态并分散循环应力。本申请的锂金属负极兼具优异的界面稳定性、界面接触性能及锂枝晶抑制效果;将其应用于电池时,可同步实现电池倍率性能、循环寿命与循环稳定性的协同提升。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122930840A_ABST
    Figure CN122930840A_ABST
Patent Text Reader

Abstract

The embodiment of the present application provides a kind of lithium metal negative electrode and its preparation method and application.The lithium metal negative electrode includes lithium metal layer and the protective layer being arranged in the at least one side of the lithium metal layer;In the direction gradually away from the lithium metal layer, the protective layer includes lithium transport layer, passivation layer and flexible layer that are sequentially stacked along the thickness direction of the lithium metal layer;The lithium transport layer includes halogen-containing organic lithium salt;The passivation layer includes halogen-containing inorganic lithium salt;The flexible layer includes low degree of polymerization organic polymer.The lithium metal negative electrode has the protective layer being composed of lithium transport layer, passivation layer and flexible layer, has excellent interface stability, interface contact performance and lithium dendrite inhibition effect, when it is applied to battery, can realize the synergistic promotion of battery rate performance, cycle life and cycle stability simultaneously.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of solid-state battery technology, and in particular to a lithium metal anode, its preparation method, and its application. Background Technology

[0002] Traditional liquid lithium-ion batteries are limited by the electrolyte system, resulting in drawbacks such as low energy density ceiling, easy leakage, and high risk of thermal runaway. Solid-state batteries replace traditional liquid electrolytes with solid electrolytes, possessing outstanding characteristics such as excellent intrinsic safety, no electrolyte leakage, wide electrochemical stability window, and strong heat resistance. They can effectively avoid the safety hazards of liquid batteries and can be adapted to high-capacity electrode material systems, making them a core research direction for next-generation high-energy-density energy storage devices.

[0003] Lithium metal anodes possess characteristics such as ultra-high theoretical specific capacity, extremely low redox potential, and low density, which can significantly improve the overall energy density of batteries and match the high energy density design requirements of solid-state batteries, making them an ideal material for solid-state battery anodes. However, under actual operating conditions, lithium metal anodes still suffer from poor interfacial contact and high interfacial impedance, making them prone to interfacial side reactions with solid electrolytes. Furthermore, they are highly susceptible to inducing disordered lithium dendrite growth during charge and discharge, leading to a decline in battery rate performance, shortened cycle life, and seriously compromising the battery's cyclic safety.

[0004] Therefore, there is an urgent need in the field to develop a lithium metal anode that combines excellent interface stability, interface contact performance, and lithium dendrite suppression, so as to achieve a synergistic improvement in battery rate performance, cycle life, and cycle stability. Summary of the Invention

[0005] This application provides a lithium metal anode, which, when applied to a battery, can achieve a synergistic improvement in battery rate performance, cycle life, and cycle stability.

[0006] This application also provides a method for preparing a lithium metal anode, which can produce a lithium metal anode with excellent interface stability, interface contact performance and lithium dendrite suppression effect.

[0007] This application also provides a battery that, thanks to the excellent lithium-ion transport capability, interface stability, and lithium dendrite suppression effect of the lithium metal anode, has excellent cycle life, rate performance, and safety and reliability, and can meet the needs of various high-end application scenarios, especially suitable for the field of high energy density solid-state lithium batteries.

[0008] In a first aspect, embodiments of this application provide a lithium metal anode, the lithium metal anode comprising a lithium metal layer and a protective layer disposed on at least one surface of the lithium metal layer; in a direction gradually moving away from the lithium metal layer, the protective layer comprises a lithium transport layer, a passivation layer and a flexible layer sequentially stacked along the thickness direction of the lithium metal layer;

[0009] The lithium transport layer comprises a halogen-containing organic lithium salt; the passivation layer comprises a halogen-containing inorganic lithium salt; and the flexible layer comprises a low-polymerization-degree organic polymer.

[0010] In one specific embodiment, the halogen-containing organolithium salt includes at least one of lithium heptafluorobutyrate, lithium pentafluoropropionate, and lithium trifluorobutyrate.

[0011] In one specific embodiment, the halogen-containing inorganic lithium salt comprises LiX, where X comprises at least one element selected from F, Cl, Br, and I; and / or,

[0012] The halogen-containing organic polymer includes at least one of the following: oligomers of vinylene carbonate and fluorovinylene carbonate.

[0013] In one specific embodiment, the thickness ratio of the protective layer to the lithium metal anode is (0.3~2):(10~200); and / or,

[0014] The thickness of the protective layer is 0.3 μm to 2 μm; and / or,

[0015] The thickness of the lithium metal anode is 10μm to 200μm.

[0016] In one specific embodiment, the thickness of the lithium transport layer is 5 nm to 100 nm; and / or,

[0017] The thickness of the passivation layer is 5 nm to 100 nm; and / or,

[0018] The thickness of the flexible layer is 0.1 μm to 1.99 μm.

[0019] In one specific embodiment, the surface roughness Ra of the flexible layer away from the passivation layer is <200 nm; and / or,

[0020] The contact angle of the liquid metal lithium on the surface of the flexible layer away from the passivation layer is <30°.

[0021] In one specific embodiment, the critical current density of the lithium metal anode is 2 mA / cm². 2 ≤CCD≤6mA / cm 2 .

[0022] Secondly, embodiments of this application provide a method for preparing a lithium metal anode, the method comprising the following steps:

[0023] In an inert atmosphere, haloorganic acids and halocarbonates are mixed to form a halogen-containing organic mixture.

[0024] The lithium metal layer is reacted with the halogen-containing organic mixture, and after standing and drying, the lithium metal anode is obtained.

[0025] The contact reaction time is ≥1 hour; in the fluorinated organic mixture, the mass percentage of the haloorganic acid is ≥0.5wt%, and the remaining components are the halocarbonate;

[0026] The reactivity of the haloorganic acid with the lithium metal layer is higher than that of the halocarbonate.

[0027] In one specific embodiment, the halogenated organic acid includes at least one selected from heptafluorobutyric acid, pentafluoropropionic acid, and trifluorobutyric acid; and / or,

[0028] The halogenated carbonate includes at least one of fluoroethylene carbonate and difluoroethylene carbonate; and / or

[0029] The contact reaction time is 1 to 10 hours; and / or,

[0030] In the halogen-containing organic mixture, the mass percentage of the haloorganic acid is 0.5wt% to 25wt%.

[0031] Thirdly, embodiments of this application provide a battery, the battery including the lithium metal anode, or the lithium metal anode prepared by the preparation method.

[0032] The lithium metal anode provided in this application comprises a protective layer consisting of a lithium transport layer, a passivation layer, and a flexible layer sequentially stacked along the thickness direction of the lithium metal layer. The lithium transport layer enables rapid lithium-ion conduction, the passivation layer provides chemical stability to the interface and physically prevents lithium dendrite penetration, and the flexible layer improves the interfacial adhesion with the solid electrolyte and disperses cycling stress. The lithium metal anode of this application exhibits excellent interfacial stability, interfacial contact performance, and lithium dendrite suppression; when applied to batteries, it can simultaneously achieve a synergistic improvement in battery rate performance, cycle life, and cycle stability. Attached Figure Description

[0033] The accompanying drawings, which are incorporated in and form part of this specification, illustrate embodiments consistent with this application and, together with the description, serve to explain the principles of this application.

[0034] Figure 1A schematic diagram of the structure of the protective layer on the surface of a lithium metal anode;

[0035] Figure 2 This is a SEM image of the cross-section of the lithium metal anode in Example 1;

[0036] Figure 3 EDS image of the cross-section of the lithium metal anode in Example 1;

[0037] Figure 4 EDS plot of the cross-section of the lithium metal anode in Comparative Example 1;

[0038] Figure 5 This is the XPS analysis diagram of the lithium metal anode of Example 1.

[0039] Explanation of reference numerals in the attached figures:

[0040] 1-Lithium metal layer; 2-Lithium transport layer; 3-Passivation layer; 4-Flexible layer.

[0041] The accompanying drawings illustrate specific embodiments of this application, which will be described in more detail below. These drawings and descriptions are not intended to limit the scope of the concept in any way, but rather to illustrate the concept of this application to those skilled in the art through reference to particular embodiments. Detailed Implementation

[0042] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions in the embodiments of this invention will be clearly and completely described below in conjunction with the embodiments of this invention. Obviously, the described embodiments are only some embodiments of this invention, not all embodiments. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.

[0043] As mentioned earlier, lithium metal anodes generally suffer from high interfacial impedance and low lithium-ion transport efficiency under actual operating conditions. Simultaneously, lithium metal is prone to interfacial side reactions with solid electrolytes, accelerating battery performance degradation, shortening lifespan, and the growth and puncture behavior of lithium dendrites can easily induce internal short circuits. To address these issues, a protective layer is often placed on the lithium metal surface, but this still cannot synergistically optimize interfacial contact, lithium dendrite suppression, and lithium-ion transport performance. Based on this, the inventors propose constructing a lithium metal anode with a three-layer protective structure, which can simultaneously solve the pain points of traditional lithium metal anodes, such as poor interfacial stability, poor solid-solid interface contact, and lithium dendrite growth and puncture, thereby significantly improving the overall electrochemical performance and safety of solid-state batteries.

[0044] The first aspect of this application provides a lithium metal anode, which includes a lithium metal layer and a protective layer disposed on at least one surface of the lithium metal layer; in a direction gradually moving away from the lithium metal layer, the protective layer includes a lithium transport layer, a passivation layer and a flexible layer sequentially stacked along the thickness direction of the lithium metal layer.

[0045] The lithium transport layer comprises a halogen-containing organic lithium salt; the passivation layer comprises a halogen-containing inorganic lithium salt; and the flexible layer comprises a low-polymerization-degree organic polymer.

[0046] The lithium metal anode provided by this invention, such as Figure 1 The protective layer shown has a three-layer structure, which can simultaneously improve interface stability, interface contact and dendrite suppression. This lithium metal anode enables the battery to have outstanding cycle stability, rate performance and safety.

[0047] Specifically, the protective layer includes a lithium transport layer, a passivation layer, and a flexible layer. The lithium transport layer is disposed on the surface of the lithium metal layer, the passivation layer is disposed on the surface of the lithium transport layer away from the lithium metal layer, and the flexible layer is disposed on the surface of the passivation layer away from the lithium transport layer.

[0048] The flexible layer comprises a low-polymerization-degree organic polymer. Through the reversible deformation adaptability of the organic polymer segments, this layer can fill micro-voids at the interface, increasing the effective contact area with the solid electrolyte, eliminating interfacial porosity, and making the migration channels for lithium ions at the solid electrolyte-anode interface more continuous and unobstructed. This effectively reduces interfacial impedance, constructs a uniform transport path for electrons and lithium ions, and prevents battery deactivation due to interfacial contact failure. Simultaneously, the flexible layer also possesses excellent elasticity, which can reduce interfacial stress concentration during battery cycling, effectively mitigating the volume expansion of the lithium metal anode and reducing the formation of interfacial cracks. It should be noted that, in addition to the low-polymerization-degree organic polymer, the flexible layer also includes alkoxy lithium (ROLi). - alkyl lithium carbonate ROCOOLi - Lithium halide alkoxy group XROLi - ROCOOLi, a type of alkyl halide lithium carbonate - Inorganic lithium salts LiX, where X includes at least one of the elements F, Cl, Br, and I.

[0049] The passivation layer comprises halogen-containing inorganic lithium salts. Benefiting from the excellent chemical stability, wide electrochemical window, and high mechanical modulus of halogen-containing inorganic lithium salts, they effectively block direct contact between lithium metal and the solid electrolyte and suppress lithium dendrite piercing behavior induced by the sharp electric field. Simultaneously, these halogen-containing inorganic lithium salts possess a low lithium-ion migration barrier, promoting lateral diffusion of lithium ions on the lithium metal anode surface and facilitating uniform lithium metal deposition, thus fundamentally suppressing internal short circuits caused by disordered lithium dendrite growth. This passivation layer achieves dual optimization of chemical passivation and mechanical stability of the lithium metal anode, significantly improving the cycle stability of the battery. It should be noted that the passivation layer, in addition to halogen-containing inorganic lithium salts, also includes halogenated organic lithium salts, vinylene carbonate and its oligomers, fluorovinylene carbonate and its oligomers, etc.

[0050] It should be noted that an "organic-inorganic hybrid interface" is formed between the flexible layer and the passivation layer. This interface combines flexibility and ionic conductivity, providing good structural adaptability, buffering the volumetric stress generated during cycling, and maintaining close contact between the solid and solid interfaces. Simultaneously, this interface possesses excellent lithium-ion conductivity, effectively mitigating localized charge accumulation and electric field distortion, promoting uniform lithium metal nucleation, and ensuring the integrity and stability of the battery's long-term cycling electrochemical interface.

[0051] The lithium transport layer comprises a halogen-containing organic lithium salt, exhibiting high lithium-ion conductivity and lithiophilicity. Within this layer, the halogen-containing organic lithium salt forms a high lithium-ion transport channel. The halogen groups in its molecular structure form weak coordination interactions with lithium ions, lowering the lithium-ion migration barrier and effectively promoting rapid lithium-ion transport. Simultaneously, it facilitates the uniform dispersion and deposition of lithium ions transported to the negative electrode on the surface of the lithium metal, forming a flat and dense deposited lithium metal layer. This effectively suppresses the growth of lithium metal dendrites and significantly optimizes the battery's rate performance. It should be noted that, in addition to the halogen-containing organic lithium salt, the lithium transport layer also includes an inorganic lithium salt, LiX, where X includes at least one of the elements F, Cl, Br, and I.

[0052] It should be noted that a lithium ion concentration gradient is formed between the passivation layer and the lithium transport layer, generating a space charge layer. The electric field effect generated by this space charge layer can effectively rectify the lithium ion transport, causing lithium ions to spontaneously transport from high potential to low potential, reducing local current density concentration, thereby inhibiting dendrite growth and promoting uniform lithium metal deposition.

[0053] The lithium metal anode of this invention features a three-layer composite protective layer. The inner lithium transport layer promotes rapid lithium-ion transport, the middle passivation layer provides both chemical passivation and mechanical barrier properties, and the outer flexible layer effectively enhances the interfacial adhesion between the lithium metal anode and the solid electrolyte, mitigating volume expansion deformation during cycling. Through the synergistic effect of the three functional layers, the interfacial stability, interfacial contact, and dendrite suppression capabilities of the lithium metal anode are simultaneously improved, thereby achieving a synergistic optimization and improvement in the rate performance, cycle life, and cycle stability of the solid-state battery.

[0054] In one specific embodiment, the halogen-containing organolithium salt includes at least one of lithium heptafluorobutyrate, lithium pentafluoropropionate, and lithium trifluorobutyrate.

[0055] Specifically, when the halogen-containing organic lithium salt is of the type mentioned above, the lithiophilic properties of the lithium transport layer can be further optimized, reducing the ion migration resistance between the lithium transport layer and the lithium metal layer, lowering the lithium ion insertion / extraction and migration barriers, and thus promoting more uniform lithium ion deposition on the surface of the lithium metal layer. The halogen-containing organic lithium salt can be selected according to the actual application and performance requirements.

[0056] In one specific embodiment, the halogen-containing inorganic lithium salt includes LiX, where X includes at least one of F, Cl, Br, and I. It should be noted that the halogen-containing inorganic lithium salt LiX is selected from LiF, LiCl, LiBr, and LiI. The strong chemical bonding between the halide anions in this type of halogen-containing inorganic lithium salt and lithium metal forms a stable Li-X covalent bond network, significantly suppressing side reactions between lithium metal and the solid electrolyte. Simultaneously, the inherently high ionic conductivity and low electronic conductivity of the halogen-containing inorganic lithium salt effectively separate the electron and lithium-ion transport paths, thereby improving the cycle stability of the battery. Furthermore, the above-mentioned type of inorganic lithium salt can further enhance the physical blocking effect of the passivation layer on lithium dendrite penetration behavior. The halogen-containing inorganic lithium salt can be selected according to the actual application and performance requirements. In a preferred embodiment, the halogen-containing inorganic lithium salt is lithium fluoride.

[0057] In one specific embodiment, the low degree of polymerization organic polymer includes at least one of vinylene carbonate oligomers and fluorovinylene carbonate oligomers.

[0058] It should be noted that oligomers of vinylene carbonate include, but are not limited to, at least one of (CHCHOCO2)2 and (CHCHOCO2)3, and oligomers of fluorovinylene carbonate include, but are not limited to, at least one of (CFCHOCO2)2 and (CFCHOCO2)3. When the low-polymerization degree organic polymer includes the above types, the flexibility and elasticity of the flexible layer are further optimized, thereby further increasing the effective contact area between the lithium metal anode and the solid electrolyte, and further enhancing the mitigation of volume deformation. Halogen-containing organic polymers can be selected according to actual applications and performance requirements.

[0059] In one specific embodiment, the thickness ratio of the protective layer to the lithium metal anode is (0.3~2):(10~200). By precisely controlling the thickness ratio of the protective layer to the lithium metal anode, the coverage of the protective layer and the lithium-ion transport path can be optimized, achieving synergistic optimization of the lithium-ion transport performance, structural stability, and dendrite suppression of the lithium metal anode. In a preferred embodiment, the thickness ratio of the protective layer to the lithium metal anode is (0.5~1):(20~50), at which point the overall performance of the lithium metal anode reaches an even better level.

[0060] In one specific embodiment, the thickness of the protective layer is 0.3 μm to 2 μm. By precisely controlling the thickness of the protective layer within this range, the protective layer can more fully cover the lithium metal layer and enhance the synergistic effect of the lithium transport layer, passivation layer, and flexible layer. Specifically, this thickness range can optimize the solid-state transport path of lithium ions and improve the cross-interface migration efficiency of lithium ions; at the same time, it makes the protective layer more compliant with changes in the volume of lithium metal, thereby improving the structural stability of the protective layer during cycling. This further achieves synergistic optimization of the ion conduction, chemical passivation, and mechanical buffering functions within the protective layer and the ion transport path of lithium ions within the protective layer. In a preferred embodiment, the thickness of the protective layer is 0.5 μm to 1 μm.

[0061] In one specific embodiment, the thickness of the lithium metal anode is 10 μm to 200 μm. By precisely controlling the thickness of the lithium metal anode within this range, the transport path of lithium ions within the lithium metal anode can be further optimized, electrochemical polarization and interfacial impedance can be further reduced, the current density distribution on the electrode surface can be optimized, and the lithium ion deposition behavior within the lithium metal anode can be further optimized. In a preferred embodiment, the thickness of the lithium metal anode is 20 μm to 50 μm.

[0062] In one specific embodiment, the thickness of the lithium transport layer is 5 nm to 100 nm. By precisely controlling the thickness of the lithium transport layer within this range, the content of halogen-containing organic lithium salts within the lithium transport layer can be effectively controlled, achieving synergistic optimization of the uniformity of lithium-ion transport channel distribution and transport rate in the lithium transport layer, thereby promoting more uniform nucleation of lithium ions on the lithium metal surface. In a preferred embodiment, the thickness of the lithium transport layer is 10 nm to 50 nm. In a more preferred embodiment, the thickness of the lithium transport layer is 20 nm to 30 nm.

[0063] In one specific embodiment, the thickness of the passivation layer is 5 nm to 100 nm. By precisely controlling the thickness of the passivation layer within this range, the content of halogen-containing inorganic lithium salts within the passivation layer can be effectively controlled, constructing a more continuous and dense physical barrier. This further suppresses interfacial side reactions between lithium metal and the solid electrolyte, and also enhances the barrier effect against lithium dendrite puncture behavior, resulting in a better level of interfacial structural stability of the lithium metal anode. In a preferred embodiment, the thickness of the passivation layer is 10 to 50 nm. In a more preferred embodiment, the thickness of the passivation layer is 10 to 20 nm.

[0064] In one specific embodiment, the thickness of the flexible layer is 0.1 μm to 1.99 μm. By precisely controlling the thickness of the flexible layer within this range, the effective contact area between the lithium metal anode and the solid electrolyte can be further optimized. Simultaneously, the buffering effect of the flexible layer on the volume deformation of the lithium metal anode during cycling is significantly enhanced, thereby further improving the internal cycle stability and safety performance of the battery. In a preferred embodiment, the thickness of the flexible layer is 100 nm to 1000 nm. In a more preferred embodiment, the thickness of the flexible layer is 200 nm to 500 nm.

[0065] In one specific embodiment, the surface roughness Ra of the flexible layer away from the passivation layer is <200 nm. The surface of the flexible layer away from the passivation layer is in direct contact with the solid electrolyte. By precisely controlling its roughness Ra to <200 nm, the solid-solid interface contact between the lithium metal anode and the solid electrolyte can be effectively improved, reducing the local porosity of the interface and increasing the effective contact area. Simultaneously, it can further optimize the mitigation of interface stress, making the electric field distribution and ion flux distribution more uniform, suppressing the generation of local high current densities, and further strengthening the suppression of lithium dendrite growth, resulting in better stability of the battery's interface structure, cycle life, and safety performance. In a preferred embodiment, Ra is 50 nm to 100 nm, at which point the overall performance of the battery is further improved.

[0066] In one specific embodiment, the contact angle of the liquid lithium metal on the surface of the flexible layer away from the passivation layer is <30°. By precisely controlling the contact angle of the liquid lithium metal on the surface of the flexible layer away from the passivation layer to be <30°, the interfacial contact resistance of the lithium metal anode can be reduced, making the interfacial charge exchange during the migration of lithium ions from the solid electrolyte to the lithium metal anode more stable and orderly, and promoting more uniform nucleation and deposition of lithium ions on the anode surface. In a preferred embodiment, the contact angle of the liquid lithium metal is 10°~20°, at which point the overall performance of the battery is further improved.

[0067] By synergistically modulating the surface roughness and the contact angle of liquid lithium metal, the compatibility between the flexible layer surface far from the passivation layer and the solid electrolyte can be further improved.

[0068] In one specific implementation, the critical current density of the lithium metal anode is 2 mA / cm². 2 ≤CCD≤6mA / cm 2 By leveraging the synergistic structure of the lithium transport layer, passivation layer, and flexible layer within the protective layer, these three elements work together to reduce the overall interfacial impedance and alleviate interfacial stress. Based on this, the critical current density (CCD) of the lithium metal anode is precisely controlled to be 2–6 mA / cm². 2 This technology effectively optimizes the uniformity of ion flux distribution at the interface, further suppressing local current concentration effects. Simultaneously, it induces lithium ions to preferentially migrate and uniformly reduce in the low-resistivity region of the interface, improving the uniformity of lithium metal deposition and thus enhancing the suppression of lithium dendrite growth. Furthermore, it optimizes the continuity and tightness of interfacial contacts and the stability of lithium ion transport, resulting in more uniform lithium deposition behavior and a more gradual increase in electrochemical polarization, significantly improving the cycle stability of the battery under high-current conditions, while simultaneously optimizing the battery's cycle life and rate performance. For example, the CCD can be 2 mA / cm². 2 3mA / cm 2 4mA / cm 2 5mA / cm 2 6mA / cm 2 Or a range consisting of any two of these values.

[0069] Secondly, this application provides a method for preparing a lithium metal anode, the method comprising the following steps:

[0070] In an inert atmosphere, haloorganic acids and halocarbonates are mixed to form a halogen-containing organic mixture.

[0071] The lithium metal layer is reacted with a halogen-containing organic mixture, allowed to stand, and dried to obtain a lithium metal anode.

[0072] The contact reaction time is ≥1 hour, and the halogenated organic mixture contains ≥0.5 wt% halogenated organic acids, with the remaining components being halogenated carbonates.

[0073] Halogenated organic acids exhibit higher reactivity with lithium metal layers than halogenated carbonates.

[0074] This invention does not limit the specific types of halogenated organic acids and halogenated carbonates, as long as they are miscible.

[0075] Specifically, halogenated organic acids have higher reactivity with lithium metal layers than halogenated carbonates. Mixing halogenated organic acids and halogenated carbonates forms an organic mixture with both acidic and halogenated activity.

[0076] A lithium metal layer is reacted with an organic mixture for at least 1 hour, with the organic mixture containing a halogenated organic acid mass percentage greater than or equal to 0.5 wt%. During the reaction, the more reactive halogenated organic acid first reacts in situ with the lithium metal layer, preferentially consuming active lithium on the surface of the lithium metal layer to form a halogenated organic lithium salt, constructing a lithium transport layer that provides a higher migration channel for lithium ions and reduces interfacial polarization. Further, the halogenated carbonate participates in the in-situ surface reaction, reacting with active lithium to generate a halogenated inorganic lithium salt, forming a passivation layer on the surface of the lithium transport layer away from the lithium metal layer. Finally, the halogenated carbonate undergoes polymerization after dehalogenation, forming a low-polymerization-degree organic polymer, which forms a flexible layer on the surface of the passivation layer away from the lithium transport layer. After the contact reaction, the mixture is left to stand in the organic mixture for 1–10 hours, followed by drying at 25–60°C under vacuum for 12 hours to obtain a lithium metal anode with a three-layer protective structure.

[0077] It should be noted that the drying process also includes a step of rinsing the lithium metal anode with a halocarbonate to remove any remaining reactants on its surface.

[0078] It should be noted that the present invention does not limit the specific implementation of the contact reaction. Exemplarily, it can be achieved by immersion treatment, including: completely immersing the lithium metal layer in a halogen-containing organic mixture, wherein the volume of the halogen-containing organic mixture is much larger than the volume of the lithium metal layer. During the immersion treatment, continuous stirring at a speed of 10-100 rpm is required.

[0079] The contact reaction can also be achieved through a coating process, specifically including: coating a halogen-containing organic mixture onto the surface of a lithium metal layer; placing a lithium metal foil horizontally on a coating machine; adding the halogen-containing organic mixture dropwise onto the surface of the lithium metal foil; using a doctor blade to evenly coat the lithium metal foil surface with the halogen-containing organic mixture; allowing it to stand for a period of time until the lithium metal and the halogen-containing organic mixture have fully reacted; and then drying it at 60°C under vacuum for 12 hours to obtain a lithium metal anode with a three-layer protective structure. The contact reaction can also be achieved through a dropwise addition process, specifically including: uniformly adding a halogen-containing organic mixture dropwise onto the surface of the lithium metal layer at a drop rate of 10 mL / min.

[0080] It should be noted that the inert atmosphere can be an argon or nitrogen protective gas atmosphere.

[0081] It should be noted that the thickness of the lithium transport layer can be controlled by adjusting the mass concentration of the haloorganic acid in the organic mixture and the contact reaction time between lithium metal and the organic mixture. The higher the mass concentration of the haloorganic acid in the organic mixture and the longer the contact reaction time between lithium metal and the organic mixture, the thicker the lithium transport layer. Similarly, the thickness of the passivation layer can be controlled by adjusting the type of halocarbonate and the contact reaction time between lithium metal and the organic mixture. The more halogen atoms in the halocarbonate and the longer the contact reaction time between lithium metal and the organic mixture, the thicker the passivation layer. Likewise, the thickness of the flexible layer can be controlled by adjusting the mass concentration of the halocarbonate in the organic mixture and the contact reaction time between lithium metal and the organic mixture. The higher the mass concentration of the halocarbonate in the organic mixture and the longer the contact reaction time between lithium metal and the organic mixture, the thicker the flexible layer.

[0082] The method for preparing the lithium metal anode of the present invention enables the simultaneous construction of functional layers for ion transport, chemical passivation, and flexible adaptation in the same preparation step, thereby improving the contact stability between the lithium metal anode and the solid electrolyte, suppressing side reactions, and contributing to uniform lithium deposition and dendrite suppression, thus improving the rate performance, cycle life, and cycle stability of the battery.

[0083] In one specific embodiment, the halogenated organic acid includes at least one of heptafluorobutyric acid, pentafluoropropionic acid, and trifluorobutyric acid.

[0084] When the aforementioned types of halogenated organic acids are selected, a more dense lithium transport layer with lower interfacial impedance can be formed on the surface of the lithium metal layer. This provides a stable structural basis for the subsequent construction of the passivation layer and flexible layer, and significantly improves the lithium-ion conductivity of the lithium transport layer, thereby optimizing the battery's rate performance. The specific type of halogenated organic acid can be selected according to the actual preparation process requirements.

[0085] In one specific embodiment, the halogenated carbonate includes at least one of fluoroethylene carbonate and difluoroethylene carbonate.

[0086] When the halogenated carbonate is of the type described above, a passivation layer with higher mechanical strength and lower lithium ion surface migration barrier can be formed on the surface of the lithium transport layer, and a flexible layer with better interfacial contact can be formed, which further improves the dendrite suppression of the prepared lithium metal anode and its adhesion to the solid electrolyte, thus significantly optimizing the cycle life, safety and rate performance of the battery.

[0087] In one specific embodiment, the contact reaction time is 1 to 10 hours. By precisely controlling the contact reaction time to 1 to 10 hours, the thickness structure of the lithium metal anode protective layer can be precisely controlled, the lithium-ion transport path of the lithium metal anode can be optimized, and thus the rate performance of the battery can be improved. In a preferred embodiment, the contact reaction time is 2 to 5 hours.

[0088] In one specific embodiment, the halogenated organic mixture contains a halogenated organic acid at a mass percentage of 0.5 wt% to 25 wt%. By controlling the mass percentage of the halogenated organic acid within this range, the thickness of the lithium metal layer and the passivation layer can be precisely controlled, thereby optimizing the rate performance of the lithium metal anode. In a preferred embodiment, the halogenated organic acid contains a mass percentage of 1 wt% to 20 wt%. In a more preferred embodiment, the halogenated organic acid contains a mass percentage of 5 wt% to 10 wt%.

[0089] Thirdly, this application provides a battery comprising the above-described lithium metal anode, or a lithium metal anode prepared by the above-described preparation method.

[0090] It should be noted that the battery includes, but is not limited to, at least one of liquid batteries, semi-solid batteries, and solid batteries. Thanks to the excellent lithium-ion transport capability, interface stability, and lithium dendrite suppression effect of the lithium metal anode of this invention, the interfacial impedance between the anode and the electrolyte can be effectively reduced, allowing the battery to maintain continuous and stable interface during charging and discharging, thereby suppressing local current concentration and lithium dendrite growth. Therefore, batteries using this lithium metal anode possess excellent cycle life, rate performance, and safety reliability, meeting the needs of various high-end application scenarios, and are particularly suitable for the field of high-energy-density solid-state lithium batteries.

[0091] The lithium metal anode of this application will be further described in detail below through specific embodiments.

[0092] Example 1

[0093] The lithium metal anode in this embodiment is prepared through the following steps:

[0094] 1) In an argon atmosphere, heptafluorobutyric acid was dissolved in fluoroethylene carbonate and stirred for 3 hours to obtain a fluorinated organic mixture containing 1 wt% heptafluorobutyric acid.

[0095] 2) Take a small piece of lithium metal foil and immerse it completely in a fluorine-containing organic mixture. Stir at 20 rpm for 4 hours and let it stand for 1 hour.

[0096] 3) Remove the lithium metal foil, rinse it three times with fluoroethylene carbonate, and vacuum dry it at 25°C for 12 hours to obtain lithium metal anode 1.

[0097] Example 2

[0098] This embodiment is basically the same as Embodiment 1, except that the heptafluorobutyric acid in step 1 is adjusted to 10 wt% of a fluorinated organic mixture. This embodiment yields lithium metal anode 2.

[0099] Example 3

[0100] This embodiment is basically the same as Embodiment 1, except that the heptafluorobutyric acid in step 1 is adjusted to 6 wt% of a fluorinated organic mixture. This embodiment yields lithium metal anode 3.

[0101] Example 4

[0102] This embodiment is basically the same as Embodiment 1, except that the heptafluorobutyric acid in step 1 is adjusted to 15 wt% of a fluorinated organic mixture. This embodiment yields lithium metal anode 4.

[0103] Example 5

[0104] This embodiment is basically the same as Embodiment 1, except that the heptafluorobutyric acid in step 1 is adjusted to 20 wt% of a fluorinated organic mixture. This embodiment yields a lithium metal anode 5.

[0105] Example 6

[0106] This embodiment is basically the same as Embodiment 1, except that the heptafluorobutyric acid in step 1 is adjusted to 25 wt% of a fluorinated organic mixture. This embodiment yields lithium metal anode 6.

[0107] Example 7

[0108] This embodiment is basically the same as Embodiment 1, except that the heptafluorobutyric acid in step 1 is adjusted to 28 wt% of a fluorinated organic mixture. This embodiment yields a lithium metal anode 7.

[0109] Example 8

[0110] This embodiment is basically the same as Embodiment 1, except that the stirring and soaking time in step 2 is adjusted to 1 hour. This embodiment yields a lithium metal anode 8.

[0111] Example 9

[0112] This embodiment is basically the same as Embodiment 1, except that the stirring and soaking time in step 2 is adjusted to 10 hours. This embodiment yields a lithium metal anode 9.

[0113] Example 10

[0114] This embodiment is basically the same as Embodiment 1, except that the stirring and soaking time in step 2 is adjusted to 11 hours. This embodiment yields a lithium metal anode 10.

[0115] Example 11

[0116] This embodiment is basically the same as Embodiment 1, except that the heptafluorobutyric acid in step 1 is adjusted to 0.5 wt% of a fluorinated organic mixture. This embodiment yields a lithium metal anode 11.

[0117] Example 12

[0118] This embodiment is basically the same as Embodiment 4, except that heptafluorobutyric acid in step 1 is replaced with trifluorobutyric acid. This embodiment yields a lithium metal anode 12.

[0119] Example 13

[0120] This embodiment is basically the same as Embodiment 4, except that the fluoroethylene carbonate in step 1 is replaced with difluoroethylene carbonate. This embodiment yields a lithium metal anode 13.

[0121] Comparative Example 1

[0122] This comparative example is basically the same as Example 1, except that fluoroethylene carbonate in step 1 is replaced with dimethyl diethanol ether. This example yields a lithium metal anode 14.

[0123] Comparative Example 2

[0124] This comparative example is basically the same as Example 1, except that heptafluorobutyric acid is not added in step 1. This example yields a lithium metal anode 15.

[0125] Comparative Example 3

[0126] This comparative example is basically the same as Example 1, except that fluoroethylene carbonate in step 1 is replaced with ethylene carbonate. This example yields a lithium metal anode 16.

[0127] Comparative Example 4

[0128] This comparative example is basically the same as Example 1, except that the stirring and soaking time in step 2 is adjusted to 0.5 hours. This example yields a lithium metal anode 17.

[0129] Comparative Example 5

[0130] This comparative example is basically the same as Example 1, except that the heptafluorobutyric acid in step 1 is adjusted to 0.4 wt% of a fluorinated organic mixture. This example yields a lithium metal anode 18.

[0131] Experimental Example 1

[0132] The following tests were performed on the lithium metal anodes of all embodiments and comparative examples.

[0133] 1. Thickness and elemental distribution detection

[0134] The longitudinal section of the lithium metal anode was imaged using a scanning electron microscope (SEM). The thickness of the lithium metal anode and the protective layer were calculated using a scale bar. (See attached image.) Figure 2 The elemental distribution of the protective layers in Example 1 and Comparative Example 1 was tested using energy-dispersive X-ray spectroscopy (EDS), and the results are shown in the figures below. Figure 3 , Figure 4 The longitudinal section of the lithium metal anode was photographed using a transmission electron microscope (TEM). The thicknesses of the inner lithium transport layer, the intermediate passivation layer, and the outer flexible layer of the protective layer were calculated using a scale bar. The results are shown in Table 1.

[0135] Depend on Figure 2 It can be seen that the lithium metal anode consists of a lithium metal layer and a protective layer.

[0136] Depend on Figure 3 , Figure 4 It can be seen that in the protective layer of the lithium metal anode of Example 1, F, O, and C elements are distributed in the protective layer. Specifically, F element is enriched in the region near the lithium metal layer, which is the lithium metal layer and passivation layer. O element is enriched in the region away from the lithium metal layer, which is the flexible layer. In the lithium metal anode of Comparative Example 1, F element is enriched in the region near the lithium metal layer. In the region where F element is enriched but away from the lithium metal layer, O and C elements are more dispersed, with no obvious enrichment areas. A continuous flexible layer is not formed on the surface of the lithium metal anode of Comparative Example 1.

[0137] 2. Detection of the types of protective layer compounds

[0138] X-ray photoelectron spectroscopy (XPS) was used to detect the chemical composition of each layer in the protective layer. Li 1s, O 1s, and C 1s valences were measured on the surface of the protective layer, and F 1s valence was measured after etching 500 nm onto the surface. The valence states and types of Li-containing compounds in the overall protective layer, the valence states and types of oligomers in the outer flexible layer, and the state of the LiF in the intermediate passivation layer were obtained. (See attached image) Figure 5 .

[0139] XPS test results of the lithium metal anode in Example 1 ( Figure 5), and combined Figure 3 , Figure 4 It can be seen that the chemical composition of the protective layer varies at different depths. Specifically, the passivation layer mainly includes characteristic peaks of LiF, belonging to halogen-containing inorganic lithium salts; the O 1s and C 1s spectra of the flexible layer show characteristic peaks of organic bonds such as CC, CO, C=O, and OCO, belonging to low-polymerization-degree organic polymers; the protective layer as a whole also includes characteristic peaks of RCO2Li, ROCO2Li, and Li2CO3, belonging to halogen-containing organic lithium salts of the lithium transport layer.

[0140] 3. Surface roughness inspection

[0141] The surface roughness Ra of the flexible layer away from the passivation layer was tested using atomic force microscopy (AFM).

[0142] 4. Contact angle detection of liquid metal lithium

[0143] The contact angle of liquid lithium metal on the surface of the flexible layer away from the passivation layer was tested using a contact angle measuring instrument.

[0144] 5. Critical Current Density CCD Test

[0145] The prepared lithium metal anode was assembled with a sulfide solid electrolyte membrane into a symmetrical battery. Using a Blue Battery Tester, under constant current charge-discharge conditions in a 25℃ constant temperature chamber, the battery was tested at 0.1 mA / cm². 2 The increasing current density was used to conduct cyclic charge-discharge tests, with each charge-discharge cycle lasting 1 hour, until the symmetrical battery failed due to short circuit or open circuit. The charge-discharge current density of the last cycle before failure was the critical current density of the tested lithium metal anode for the sulfide solid electrolyte.

[0146] Table 1. Parameters of Lithium Metal Anode

[0147]

[0148] Experimental Example 2

[0149] 1. Battery assembly

[0150] Positive electrode preparation: Lithium nickel cobalt manganese oxide (NCM), sulfide solid electrolyte (LPSCl), carbon nanofibers (VGCF), and polytetrafluoroethylene (PTFE) were mixed in a mass ratio of 85:13:1:1, and then the positive electrode was prepared by dry rolling. The positive electrode loading was 20 mg / cm³. 2 .

[0151] Solid electrolyte membrane preparation: LPSCl and PTFE were mixed at a mass ratio of 95:5, and then rolled to prepare a solid electrolyte membrane. The membrane thickness was 50 μm.

[0152] Full cell assembly: In an argon glove box, the lithium metal anode, solid electrolyte membrane, and NCM cathode prepared in the examples and comparative examples were sequentially placed into the ceramic core of the mold battery. After the battery was assembled, it was assembled for 1 minute under a pressure of 500 MPa. The assembled mold battery was then placed in a stainless steel test fixture and a test pressure of 25 MPa was applied to perform electrochemical performance testing.

[0153] 2. Cyclic life testing

[0154] The capacity retention rate of each battery assembled in step 1 was tested. The specific test method was as follows: At 25°C, the battery was first charged at a constant current rate of 0.2C to 4.25V, then charged at a constant voltage rate of 0.05C to 4.25V, and then discharged at a discharge rate of 0.2C to 2.5V. This charge-discharge cycle was repeated twice to complete the battery activation. Subsequently, the battery was charged at a constant current rate of 1C to 4.25V, then charged at a constant voltage rate of 0.05C to 4.25V, and then discharged at a discharge rate of 1C to 2.5V. This charge-discharge cycle was repeated 200 times. The discharge capacity Q1 at the first cycle and the discharge capacity Q at the 200th cycle were measured. 200 The capacity retention rate Q (in %) after 200 cycles is calculated using the following formula.

[0155] Q=Q 200 / Q1×100%.

[0156] 3. Cyclic stability test

[0157] The cycle stability of each battery assembled in step 1 was tested. The specific test method was as follows: at 25℃, the battery was first charged at a constant current rate of 0.2C to 4.25V, then charged at a constant voltage rate of 0.05C to 4.25V, and then discharged at a discharge rate of 0.2C to 2.5V. This charge-discharge cycle was repeated twice to complete the battery activation. Subsequently, the battery was charged at a constant current rate of 1C to 4.25V, then charged at a constant voltage rate of 0.05C to 4.25V, and then discharged at a discharge rate of 1C to 2.5V. This charge-discharge cycle was repeated 200 times. The AC impedance R1 of the battery after the first cycle and the AC impedance R after the 200th cycle were measured. 200 The internal resistance growth rate R (in %) after 200 cycles is calculated using the following formula.

[0158] R=R 200 / (R 200 -R1)×100%.

[0159] 4. Ratio Performance Testing

[0160] The rate capacity retention rate of each battery assembled in step 1 was tested. The specific test method was as follows: at 25°C, the battery was first charged at a constant current rate of 0.2C to 4.25V, then charged at a constant voltage rate of 0.05C to 4.25V, and then discharged at a discharge rate of 0.2C to 2.5V. This charge-discharge cycle was repeated twice to complete the battery activation. Subsequently, the battery was charged and discharged three times at a rate of 0.2C. The discharge capacity of each discharge cycle was measured and the average value was taken as the reference capacity C0.

[0161] Next, a stepped charge-discharge test was performed in the order of 0.2C, 0.5C, 1C, 2C, 3C, and 5C. At each rate, the device was first charged at a constant current to 4.25V, then charged at a constant voltage of 0.05C to 4.25V, and then discharged at the same rate to 2.5V. This charge-discharge cycle was repeated once at each rate, and the device was allowed to rest for 10 minutes after each rate test. After the stepped test, the discharge capacity C at each rate was recorded. n (n corresponds to 0.5C, 1C, 2C, 3C, 5C), calculate the capacity retention η at each rate using the following formula. n η2 represents the capacity retention rate at a 2C rate.

[0162] η n =(C n / C0)×100%.

[0163] Table 2 Electrochemical performance of the battery

[0164]

[0165] As shown in Tables 1 and 2, Comparative Examples 2 and 5 lack a lithium transport layer, hindering rapid lithium ion transport and resulting in poor 2C rate capacity retention. Comparative Example 3 lacks a passivation layer, failing to effectively suppress lithium dendrite growth and exhibiting poor cycle performance. Comparative Examples 1 and 4 lack both passivation and flexible layers; their lithium transport layers directly contact the solid electrolyte, but the effective contact area is limited. Consequently, after 200 cycles, the capacity retention, internal resistance growth rate, and 2C capacity retention all significantly deteriorate.

[0166] Compared to Comparative Examples 1-5, the batteries using lithium metal anodes in Examples 1-13 still exhibited high capacity retention after 200 cycles, with internal resistance growth rates all less than 21%, and capacity retention rates exceeding 80% at 2C rate. However, in Example 10, the contact reaction time was excessively long (11 hours), resulting in an excessively thick flexible layer. This led to slightly inferior overall battery performance compared to the other examples, but it was still superior to the comparative examples.

[0167] Thanks to the self-generated three-layer protective structure on the lithium metal surface, the inner lithium transport layer and the middle passivation layer effectively improve the lithium-ion transport rate while suppressing the growth of lithium metal dendrites, thus enhancing the battery's cycle stability and rate performance. The outermost flexible layer ensures sufficient contact between the lithium metal anode and the solid electrolyte interface, effectively improving lithium-ion transport efficiency, preventing interface deterioration, and reducing the battery's internal resistance. The lithium metal anode of this invention achieves a synergistic improvement in battery rate performance, cycle life, and cycle stability.

[0168] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A lithium metal anode, characterized in that, The lithium metal anode includes a lithium metal layer and a protective layer disposed on at least one surface of the lithium metal layer; in a direction gradually moving away from the lithium metal layer, the protective layer includes a lithium transport layer, a passivation layer and a flexible layer stacked sequentially along the thickness direction of the lithium metal layer; The lithium transport layer comprises a halogen-containing organic lithium salt; the passivation layer comprises a halogen-containing inorganic lithium salt; and the flexible layer comprises a low-polymerization-degree organic polymer.

2. The lithium metal anode according to claim 1, characterized in that, The halogen-containing organolithium salt includes at least one of lithium heptafluorobutyrate, lithium pentafluoropropionate, and lithium trifluorobutyrate; and / or, The halogen-containing inorganic lithium salt includes LiX, where X includes at least one of the elements F, Cl, Br, and I; and / or, The low degree of polymerization organic polymer includes at least one of the following: oligomers of vinylene carbonate and oligomers of fluorovinylene carbonate.

3. The lithium metal anode according to any one of claims 1-2, characterized in that, The thickness ratio of the protective layer to the lithium metal anode is (0.3~2):(10~200).

4. The lithium metal anode according to any one of claims 1-3, characterized in that, The thickness of the protective layer is 0.3 μm to 2 μm; and / or, The thickness of the lithium metal anode is 10μm to 200μm.

5. The lithium metal anode according to any one of claims 1-4, characterized in that, The thickness of the lithium transport layer is 5nm~100nm; and / or, The thickness of the passivation layer is 5 nm to 100 nm; and / or, The thickness of the flexible layer is 0.1 μm to 1.99 μm.

6. The lithium metal anode according to any one of claims 1-5, characterized in that, The surface roughness Ra of the flexible layer away from the passivation layer is <200 nm; and / or, The contact angle of the liquid metal lithium on the surface of the flexible layer away from the passivation layer is <30°.

7. The lithium metal anode according to any one of claims 1-6, characterized in that, The critical current density of the lithium metal anode is 2 mA / cm². 2 ≤CCD≤6mA / cm 2 .

8. A method for preparing a lithium metal anode according to any one of claims 1-7, characterized in that, The preparation method includes the following steps: In an inert atmosphere, haloorganic acids and halocarbonates are mixed to form a halogen-containing organic mixture. The lithium metal layer is reacted with the halogen-containing organic mixture, and after standing and drying, the lithium metal anode is obtained. The contact reaction time is ≥1 hour; in the halogen-containing organic mixture, the mass percentage of the haloorganic acid is ≥0.5wt%, and the remaining components are the halocarbonates; The reactivity of the haloorganic acid with the lithium metal layer is higher than that of the halocarbonate.

9. The method for preparing a lithium metal anode according to claim 8, characterized in that, The halogenated organic acid includes at least one selected from heptafluorobutyric acid, pentafluoropropionic acid, and trifluorobutyric acid; and / or... The halogenated carbonate includes at least one of fluoroethylene carbonate and difluoroethylene carbonate; and / or The contact reaction time is 1 to 10 hours; and / or, In the halogen-containing organic mixture, the mass percentage of the haloorganic acid is 0.5wt% to 25wt%.

10. A battery, characterized in that, The battery comprises a lithium metal anode as described in any one of claims 1 to 6, or a lithium metal anode prepared by the method described in any one of claims 7 to 9.